Hak Anak Dalam Hadis : Analisis Maqasid Syariah Dan Relevansi Perlindungan Anak Kontemporer - Nur Afifa Maharani; Tasliyah Erlina Ramli; Amrudin (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
Child protection remains a critical issue despite the presence of various national and international legal instruments. Within Muslim societies, the Prophetic traditions (hadith) hold significant normative and ethical authority, yet existing studies often remain limited to textual-normative interpretations and are not sufficiently developed to address contemporary child protection challenges. This study aims to examine children’s rights in hadith and analyze them through the lens of maqasid shariah to assess their relevance to contemporary child protection frameworks. The research employs a qualitative library research design with a normative-analytical approach, utilizing thematic content analysis. Primary data consist of canonical hadtth collections concerning children’s rights, including the prohibition of infanticide, the obligation of education, justice in parental treatment, and economic maintenance. Secondary data include scholarly works published in the past five years on hadith studies, maqasid theory, and child protection. The findings reveal that hadith establishes core rights for children: the right to life and safety, the right to lineage and identity, the right to education and moral upbringing, equitable treatment, and adequate financial support. Within the maqāṣid framework, these rights correspond to the preservation of life, intellect, lineage, religion, and wealth, demonstrating substantial compatibility with contemporary child protection principles.